Tick-borne encephalitis virus: an emerging virus in Scandinavia - Lamsal, Alaka (University of South-Eastern Norway, 2024)
Tick-borne encephalitis virus (TBEV) causes Tick-borne encephalitis (TBE) which is an infection of the central nervous system that can lead to encephalitis. TBE cases are increasing in Scandinavia over the last few decades posing a concern to public health. The geographical spread of TBEV can be caused by favourable climatic conditions due to ongoing climatic changes. This PhD thesis aims to gain a comprehensive understanding on the status of TBEV distribution in Norway, Sweden, and Denmark. TBEV distribution differs along geographical regions in Scandinavia due to distinct climatic and ecological conditions. TBEV circulation was found to be widespread in coastal and lowland areas, with multiple foci capable of initiating endemic regions. In alpine regions, where little is known about tick distribution, reindeer were sero-screened as sentinel animals. Antibodies against TBEV was not detected in reindeer populations indicating that tick that carry TBEV may not have reached in reindeer foraging regions. However, the inclusion of recent data and other deer species as sentinels for monitoring could be helpful. Human incidence of TBE clusters around specific coastal regions despite widespread geographical distribution of TBEV. The TBEV-Eu strain often presents with mild symptoms, that can be mistaken as flu or other illness. Retrospective sero-analysis of patients with CNS symptoms found one underreported case that show loopholes in TBE reporting system. This resonates with underestimation of TBE cases concluded from earlier studies. A whole genome sequencing methodology for TBEV strains was established in the reference laboratory for TBE in Norway. This approach facilitates bioinformatic and phylogenetic analysis which are important for tracking TBEV spread and its future trajectory in Scandinavia. This established technique can serve as a reference for sequencing low viral load strains typical from ticks and human cases. publishedVersion